2007
DOI: 10.1088/1475-7516/2007/01/006
|View full text |Cite
|
Sign up to set email alerts
|

String-inspired cosmology: a late time transition from a scaling matter era to a dark energy universe caused by a Gauss–Bonnet coupling

Abstract: The Gauss-Bonnet (GB) curvature invariant coupled to a scalar field φ can lead to an exit from a scaling matter-dominated epoch to a late-time accelerated expansion, which is attractive to alleviate the coincident problem of dark energy. We derive the condition for the existence of cosmological scaling solutions in the presence of the GB coupling for a general scalar-field Lagrangian density p(φ, X), where X = −(1/2)(∇φ) 2 is a kinematic term of the scalar field. The GB coupling and the Lagrangian density are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
100
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(104 citation statements)
references
References 106 publications
3
100
0
Order By: Relevance
“…The addition of a non-linear function of the Ricci scalar R to the Einstein-Hilbert action has been demonstrated to cause acceleration for a wide variety of f (R) functions [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,…”
Section: Introductionmentioning
confidence: 99%
“…The addition of a non-linear function of the Ricci scalar R to the Einstein-Hilbert action has been demonstrated to cause acceleration for a wide variety of f (R) functions [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,…”
Section: Introductionmentioning
confidence: 99%
“…In [23] the GB correction was proposed to study the dynamics of dark energy, where it was found that quintessence or phantom phase may occur in the late time universe. Different aspects of accelerating cosmologies with GB correction have been also discussed in [24], [25], [26], [27], [28], [29]. The modified GB theory applied to dark energy has been suggested in [30], and further studies of the modified GB model applied to late time acceleration, have been considered among others, in [31], [32], [33], [34], [35].…”
Section: Introductionmentioning
confidence: 99%
“…It is tempting to study the string curvature corrections to Einstein gravity amongst which the Gauss-Bonnet correction enjoys special status. A large number of papers are devoted to the cosmological implications of string curvature corrected gravity [2,3,4,5,6,7,8,9,10,11]. These models suffer from several problems.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the Gauss-Bonnet theory with dynamical dilaton might cause transition from matter scaling regime to late time acceleration allowing to alleviate the fine tuning and coincidence problems. However, it is difficult to reconcile this model with nucleosynthesis [4,5]. Another possibility of large scale modification is provided by non-locally corrected gravity which typically involves inverse of d'Alembertian of Ricci scalar.…”
Section: Introductionmentioning
confidence: 99%